Reactor design and techno-economic analysis for chemical looping hydrogen production - Kataria, Priyam (Curtin University, 2023)
This project describes several aspects of process design for chemical looping hydrogen production technology. Multi-dimensional model of the reactor system is represented through dynamic simulations, demonstrating optimum conversions under isothermal operation. The optimal conditions are then utilized for developing a reactor design capable of exhibiting gas-solid reactions. A techno-economic assessments is further conducted, which highlights profitability and efficiency of the proposed system compared to the conventional Steam Methane Reforming.